Lama, pula ja työttömyys : tamperelaisperheiden toimeentulo 1928-1938 - Peltola, Jarmo (Tampere : Tampere University Press, 2008)
Summary: Depression, shortage and unemployment : the livelihood of Tampere families in 1928-1938 : The depression of the 1930s in the industrial city II.
Väitöskirja
tvasen
Keywords: 1930-luku; 1930-talet; lama; sosiaaliset vaikutukset; köyhät; köyhyys; köyhäinhoito; toimeentulo; perheet; työläiset; työttömät; työttömyys; rikollisuus; arki; sosiaalihistoria; mikrohistoria; recession; sociala effekter; fattiga; fattigdom; fattigvård; utkomst; familjer; arbetare; arbetslösa; arbetslöshet; brottslighet; vardag; socialhistoria; mikrohistoria; Tampere; Tammerfors; opinnäytteet -- vasen; väitöskirjat; doktorsavhandlingar